Clopidogrel versus prasugrel in rabbits - Wong, Pancras C.; Watson, Carol A.; Hua, Ji; Schumacher, William A.; Rehfuss, Robert (Thrombosis and Haemostasis, 2009)
The new P2Y12 antagonist prasugrel produces greater inhibition of ADP-induced platelet aggregation (IPA) and reduction of thrombotic events in patients versus approved doses of clopidogrel, but increases major bleeding. We examined whether IPA level or P2Y12 receptor occupancy (RO) could be optimized to better balance the efficacy and bleeding effects of these thienopyridines and reduce the response variability in rabbits. Rabbits were given three daily oral doses of clopidogrel (0.3–30 mg/ kg/d), prasugrel (0.03–10 mg/kg/d) or vehicle (n=6–40/group). Electrically-induced carotid artery thrombosis (AT, % thrombus weight reduction), cuticle bleeding time (BT, fold-increase over control), IPA to 20 μM ADP (% inhibition of peak light transmission) and RO (% inhibition of [33P]-2MeS-ADP binding to P2Y1-blocked platelets) were determined 2–3 hours after the last dose. ED50 (doses for half-maximal effect, mg/kg/d) of AT, BT, IPA and RO were 1.6, 6.7, 1.9 and 1.4 for clopidogrel vs. 1.2, 1.9, 0.5 and 0.2 for prasugrel. IPA of 30–40% for both compounds produced the optimal balances of efficacy (AT: 50–60%) and BT of about 2-fold with significant RO of 70–80%. IPA of 50–60% achieved higher efficacy (AT: 60–80%), but with increased BT of five- to six-fold and >90% RO. Box-plot suggests no significant difference in the IPA and RO response variability between both compounds. Clopidogrel was 1.3–7 times less potent than prasugrel in rabbits, depending upon which biomarker was studied. The ratio of efficacy:bleeding was most favorable at a moderate IPA of 30% to 40%. Both compounds had similar IPA and RO response variability.
Keywords: Clopidogrel; haemostasis; platelet aggregation; prasugrel; thrombosis